2004
DOI: 10.1254/jphs.94.277
|View full text |Cite
|
Sign up to set email alerts
|

Modulation of Capsaicin-Evoked Visceral Pain and Referred Hyperalgesia by Protease-Activated Receptors 1 and 2

Abstract: Abstract. Protease-activated receptors (PARs) 1 and 2 are expressed in capsaicin-sensitive sensory neurons, being anti-and pro-nociceptive, respectively. Given the possible cross talk between PAR-2 and capsaicin receptors, we investigated if PAR-2 activation could facilitate capsaicin-evoked visceral pain and referred hyperalgesia in the mouse and also examined the effect of PAR-1 activation in this model. Intracolonic (i.col.) administration of capsaicin triggered visceral pain-related nociceptive behavior, f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
41
1

Year Published

2005
2005
2015
2015

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 59 publications
(45 citation statements)
references
References 30 publications
3
41
1
Order By: Relevance
“…In agreement with previous studies, 11,12,33 we found that intracolonic capsaicin evoked concentration-dependent visceral pain-related behaviors and referred mechanical hyperalgesia. The number of capsaicin-induced pain-related behaviors was significantly lower in σ 1 -KO mice than in WT mice.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…In agreement with previous studies, 11,12,33 we found that intracolonic capsaicin evoked concentration-dependent visceral pain-related behaviors and referred mechanical hyperalgesia. The number of capsaicin-induced pain-related behaviors was significantly lower in σ 1 -KO mice than in WT mice.…”
Section: Discussionsupporting
confidence: 93%
“…11,12 The intracolonic capsaicin model in mice may represent an appropriate translational model of visceral pain, because application of capsaicin to the human gut evokes intense (acute) pain and referred mechanical hyperalgesia and is a well-validated human model of visceral pain. [13][14][15] Sigma receptors have been classified into two distinct subtypes, sigma-1 (σ 1 ) and sigma-2 (σ 2 ), although only the σ 1 receptor has been cloned.…”
mentioning
confidence: 99%
“…Prestimulation with PAR 4 activating peptide can significantly reduce allodynia and hyperalgesia in response to PAR 2 and TRPV4 agonists and can effectively inhibit elevated intracellular Ca 2+ levels in primary afferent neurons in response to these agonists (Auge et al, 2009). Intracolonic PAR 1 activation similarly reduces behavioral responses, indicative of antinociceptive regulation of visceral pain (Kawao et al, 2004).…”
Section: Protease-dependent Sensitization Of Transient Receptor Potenmentioning
confidence: 92%
“…The TRPV1 antagonist capsazepine blocks PAR 2 -mediated thermal hyperalgesia, but not spontaneous nociceptive behavior or Fos expression, showing that sensitization/transactivation of TRPV1 by PAR 2 might be involved in thermal hyperalgesia but not in the primary pain message [62]. In a model of visceral pain induced by intracolonic administration of capsaicin, intracolonic injection of PAR 2 agonist, 6 or 18h before capsaicin, produces a delayed sensitization of capsaicin receptors, resulting in facilitation of visceral pain and referred hyperalgesia in response to von Frey filaments stimuli [63]. In the same study, authors have shown that PAR 1 activation appears to play an antinociceptive role in processing of visceral pain in this model [63].…”
Section: Interaction Of Protease-activated Receptors With Transient Rmentioning
confidence: 96%
“…In a model of visceral pain induced by intracolonic administration of capsaicin, intracolonic injection of PAR 2 agonist, 6 or 18h before capsaicin, produces a delayed sensitization of capsaicin receptors, resulting in facilitation of visceral pain and referred hyperalgesia in response to von Frey filaments stimuli [63]. In the same study, authors have shown that PAR 1 activation appears to play an antinociceptive role in processing of visceral pain in this model [63]. To study the relationship between PAR 2 and TRPV1, Amadesi and colleagues used four different approaches: calcium signaling in HEK cells co-transfected with PAR 2 and TRPV1, calcium signals in DRGs, electrophysiology approach, and in vivo experiments [60].…”
Section: Interaction Of Protease-activated Receptors With Transient Rmentioning
confidence: 99%